Analisis Strategi Pemasaran Sapi Qurban pada Peternakan Purnomo Sapi Mulyo - Samuel Barita Manurung; Muhammad Syihabuddin (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2026)
This study aims to analyze the marketing strategy of sacrificial cattle implemented by Purnomo Sapi Mulyo Farm in Boyolali Regency. The analysis focuses on the application of the marketing mix, customer satisfaction and loyalty, as well as the utilization of digital marketing in enhancing business competitiveness. A qualitative approach with a descriptive research design was employed. Data were collected through in-depth interviews and direct observations of marketing activities and business operations, with the farm owner serving as the main informant. Data analysis was conducted using qualitative descriptive techniques through data reduction, data display, and conclusion drawing. The results indicate that the farm’s marketing strategy primarily emphasizes product quality, fulfillment of customer expectations, and long-term relationships based on trust. Customer satisfaction is achieved through the provision of healthy cattle that meet religious requirements, accompanied by transparent service guarantees. Customer loyalty is reflected in repeat purchases and word-of-mouth recommendations. In addition, the strategic business location contributes to ease of access and purchasing decisions. Regarding digital marketing, social media platforms have been utilized as information channels; however, their use remains largely informative and has not been optimized in terms of interactivity and entertainment. This study contributes theoretically by reinforcing the relevance of customer satisfaction, loyalty, and digital marketing concepts within the sacrificial cattle farming sector. Practically, the findings provide insights for livestock business actors to develop more adaptive, creative, and sustainable marketing strategies in response to changing market dynamics.